2015
DOI: 10.1016/s0924-9338(15)31916-7
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety in Adolescents with Congenital Heart Disease

Abstract: Introduction:Adolescents with congenital heart disease are at increased risk for developingpsychological distress. Aim of the study: To assess the prevalence of depression and anxiety in adolescents withcongenital heart disease, and to identify the predictors related to thesedisorders. Methods:This is a cross-sectional case-control study. A total of 60 adolescents withCHD aged from 12-18 years and 30 apparently healthy adolescents were recruited.All participants were assessed using a designed questionnaire, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Similarly, a study from Ethiopia revealed that the presence of medical illness increased the risk of depression [ 4 ], and a study in Cameroon [ 33 ] reported that the presence of chronic diseases increased the risk of depression. Awaad et al [ 40 ] also reported that adolescents with chronic heart disease were at increased risk of depression. This might be because health problems not only affect daily activities but also school attendance, which in turn affects the psychological well-being of children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study from Ethiopia revealed that the presence of medical illness increased the risk of depression [ 4 ], and a study in Cameroon [ 33 ] reported that the presence of chronic diseases increased the risk of depression. Awaad et al [ 40 ] also reported that adolescents with chronic heart disease were at increased risk of depression. This might be because health problems not only affect daily activities but also school attendance, which in turn affects the psychological well-being of children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression have deleterious effects on physical and psychological health of children and adolescents with CHDs, especially in the presence of low levels of education and severe cardiac ailments. 15 In the last decade, due to progress in overall management there are increased number of teenagers with CHD who achieve adulthood. In developing countries like Pakistan, we even encounter adolescents with unrepaired CHDs.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show higher rates of behavior disorders whereas others failed to prove so. [15][16][17] Etiology of anxiety and depression is multifactorial. In a developing country like Pakistan along with the main disease, accessibility and affordability of health services is also a contributory factor.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of anxiety disorders has been found to range from 5 to 50% in children with chronic medical conditions such as asthma, epilepsy, and diabetes 4 and 26 to 30% in children with CHD. [5][6][7] Increased anxiety symptoms and diagnoses in these populations compared to the general population may be related to childhood medical trauma as a result of separation from parents, long and frequent hospitalisations, exposure to painful procedures shortly after birth, and potential modifiable aspects of parental mental health (e.g., anxiety). 8,9 The consequences of anxiety in childhood are significant, have long-term effects on individuals' lives, and contribute to preventable hospital and societal costs.…”
mentioning
confidence: 99%
“…13 Other studies have found the presence of anxiety symptoms in older children, adolescents, and adults with CHD in 26-30% of patients. [5][6][7]14 Thus, at younger ages and throughout the lifespan,…”
mentioning
confidence: 99%